Notas sobre la estructura de la propiedad en la fase de despegue de la minería leonesa, 1890-1914 (Estudios humanísticos. Geografía, historia y arte, 1989)
This study deals with the period when the mining boom led to the registration of large arcas in the province of León as a provision for the exploitation of their mineral resources.We will try to find out who made the registrations, where the concessions were located, and the dimensions of the mining property.